Первая находка в СССР комара Aedes (Finlaya) versicolor Ваrraud (Diptera, Culicidae), описание его самки и личинки IV стадии - Данилов, В.Н. (Вестник зоологии, 1978)
Female and larve of instar IV of A. (F.) versicolor Barraud, new for the fauna of the USSR, are described. This species known formerly from the Western Himalayas only was found in the Talysh foothills (Lenkoran district, Azerbaijan SSR). The morphology of its larva described for the first time allows to resurrect A. versicolor from a variety of A. (O.) pulchritarsis Rond. to a distinct species and to transfer it from the subgenus Ochlerotatus to the subgenus Finlaya, i. e. to return it to its original taxonomic status (Barraud, 1924). The discovery of A. versicolor may be expected also in the mountain regions of Afghanistan, Middle Asia, Iran and Turkey.